(untitled) (Journal of Monno Medical College, 2022)
Background: The acromion is a process on the scapula of pectoral girdle and articulates the clavicle. The morphometry of the acromion process, it’s relation to coracoid process and supraglenoid tubercle is important to determine dimensions of the subacromial space. Variations of acromion process and subacromial space can encourage clinical conditions of subacromial impingement syndrome, rotator cuff diseases and degenerative changes. Objective: Aim of this study was to determine the morphometric values of acromion process and thereby help managing the related clinical conditions as well as for the anthropological studies. Methodology: The study was completed on 140 dry adult human left scapulae derived from 89 males and 51 females. Morphometry of the acromion process of the scapulae was measured with the help of digital Sliding Calipers and metallic wire and scale. Results: The average maximum length of acromion process was 53.22 (±6.17) mm and 46.20 (±4.99) mm, maximum (average) width of acromion process was 29.83 (±3.05) mm and 26.25 (±3.03) mm, acromio-coracoid distance was 36.72 (±5.86) mm and 32.95 (±4.09) mm, acromio-glenoid distance was 29.98 (±3.97) mm and 27.17 (±3.38) mm among males and females respectively. Conclusion: Morphometric knowledge of the study might be useful for the Orthopaedic Surgeons and the Radiologists for determination of gender and for the Anthropologists when studying the evolution of bipedal gait. J Monno Med Coll June 2022;8(1): 10-12